EDUKASI DAN PEMBUATAN TAMAN OBAT KELUARGA UNTUK PENCEGAHAN DAN PEMELIHARAAN KESEHATAN MASYARAKAT - Suryani Suryani; Henny Kasmawati; La Ode Muh. Fitrawan; Nurull Hikmah; Nurramadhani A Sida; Ruslin Ruslin; Aswani Aswani (Jurnal Pengabdian NUSANTARA, 2022)
Indonesian people have used herbal ingredients for health. However, there are differences in natural resources and knowledge of plant processing techniques in medicine which differ from region to region. This community service aims to increase public knowledge about the types of plants that can be cultivated in  Family Medicine Garden and their health benefits. Educational activities and the establishment of a Family Medicine Garden (TOGA) were held at the UHO Faculty of Pharmacy drug park. The method of educational activities is in the form of lectures and question-and-answer interactions, followed by manufacturing and planting medicinal plants at  Family Medicine Garden. Education is carried out by introducing the efficacy of 21 plants, the parts used and the benefits of  Family Medicine Garden. The activity went well, and the community was enthusiastic about getting new knowledge about types of plants and how to make  Family Medicine Garden.